Diurnal variations in luminal and stromal areas of choroid in normal eyes - Kinoshita, Takamasa (Br J Ophthalmol, 2017)
AIMS: To determine the diurnal variations of the luminal and stromal areas of the choroid in normal eyes. METHODS: This was a prospective observational study of 38 eyes of 38 normal subjects. The blood pressure, heart rate, intraocular pressure and enhanced depth imaging optical coherence tomographic (EDI-OCT) images were recorded every 3 hours between 6:00 and 21:00 hours. The horizontal EDI-OCT images of the subfoveal choroid were converted to binary images. The central choroidal thickness (CCT), total cross-sectional choroidal area, the luminal areas, stromal areas and the ratio of luminal area to total choroidal area (L/C ratio) were determined. RESULTS: There were significant diurnal variations in the CCT, total choroidal area, luminal area and L/C ratio with the maximum values at 6:00 hours and the minimum values at 15:00 hours (p<0.001 for the CCT, p=0.011 for the total choroidal area, p<0.001 for the luminal area and p=0.014 for the L/C ratio). There was no significant variation in the stromal area (p=0.216). The range of fluctuation in the CCT was significantly correlated with that in the luminal area and the total choroidal area (p<0.001). However, there was no significant correlation between the fluctuation range in the CCT and that in the stromal area (p=0.095). There was no statistical relationship between the systemic parameters and the choroidal parameters. CONCLUSIONS: The changes in the luminal area are most likely responsible for the diurnal change in the CCT and subfoveal choroidal area. TRIAL REGISTRATION NUMBER: UMIN000019060, Pre-results.